การซึมผ่านของหมึกปากกาเคมีผ่านถุงพลาสติกใส่อาหาร - Lohasiriwat, Pongsakorn (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2024)
Permanent Ink Permeability through Plastic Bag for Food Packaging Pongsakorn Lohasiriwat รับบทความ: 6 กรกฎาคม 2566; แก้ไขบทความ: 17 มีนาคม 2567; ยอมรับตีพิมพ์: 30 มีนาคม 2567; ตีพิมพ์ออนไลน์: 3 พฤษภาคม 2567 บทคัดย่อ การซื้ออาหารพร้อมรับประทานในประเทศไทยเป็นสิ่งที่พบเห็นได้โดยทั่วไป บรรจุภัณฑ์ที่ผู้ขายเลือกใช้มีหลายรูปแบบและผลิตขึ้นจากวัสดุหลายชนิด เช่น พลาสติก กระดาษ กล่องโฟม ขวดแก้ว บรรจุภัณฑ์จากวัสดุธรรมชาติ ปัจจุบันยังพบว่า ผู้ขายนิยมใช้ปากกาเคมีในการเขียนรายละเอียดลงบนภาชนะบรรจุเพื่อบ่งบอกชนิดอาหาร ซึ่งหมึกปากกาเคมีเป็นสารเคมีที่ไม่เหมาะสมต่อการบริโภค และก่อให้เกิดโทษต่อสุขภาพได้ การศึกษาครั้งนี้ทดสอบความเป็นไปได้ของการซึมผ่านหมึกปากกาเคมี 4 ยี่ห้อ เมื่อเขียนลงบนบรรจุภัณฑ์ถุงพลาสติก 3 ประเภท ได้แก่ ถุงร้อนแบบขุ่น ถุงร้อนแบบใส และถุงเย็น โดยทดสอบถุงบรรจุน้ำร้อนเป็นเวลา 60 นาที ภายใต้สภาพการมีความชื้น และไม่มีความชื้น ผลการทดสอบพบว่า 1) ถุงพลาสติกเย็นก่อให้เกิดการซึมผ่านของหมึกปากกามากที่สุด ตามด้วยถุงร้อนแบบขุ่น ส่วนถุงร้อนแบบใสมีการซึมผ่านน้อยที่สุด 2) หากถุงเปียกเกิดการซึมผ่านของหมึกเคมีได้มากกว่าถุงแห้ง และ 3) ปากกาเคมีแต่ละยี่ห้อส่งผลต่อการซึมผ่านของหมึกแตกต่างกัน จากการศึกษาสรุปได้ว่า ผู้ขายควรหลีกเลี่ยงการใช้ปากกาเคมีเขียนลงบนบรรจุภัณฑ์อาหาร ระวังความเปียกชื้นภายนอกถุงโดยเช็ดแห้ง และควรเลือกใช้ถุงให้ถูกประเภท คำสำคัญ: บรรจุภัณฑ์อาหาร หมึกปากกาเคมี การซึมผ่าน ความชื้น Abstract The ready–to–eat food is common in many regions of Thailand. There are various types of packaging that sellers has chosen from materials such as plastic, paper, foam box, glass bottle and packaging using natural materials. At present, many sellers still use permanent chemical markers to write on the food packages to identify the packed food. The permanent ink is a chemical which is unsuitable for consuming and can lead to health risks. This study aimed to investigate the possibility of ink permeability under various conditions. Testing factors included four brands of blue ink permanent pens and three types of plastic bag, i.e., high–density polyethylene bag (HD), polypropylene bag (PP) and low–density polyethylene bag (PE). The testing was conducted with bags containing hot water for sixty minutes under with and without moisture outside the bag. The results revealed that 1) PE bag was the most permeability of the ink, following by HD bag. PP bag was the least ink permeability, 2) if the bag is wet outside (moisture condition), the ink diffusion had to be increased, and 3) each marker brand had different ink permeability. As results, it summarized to avoid using permanent markers to write on the hot food packages. The moisture outside the packaging is also awareness by wipe it out, and the bag types has been chosen correctly. Keywords: Food packaging, Permanent ink, Permeability, Moisture